The future direction of the Dental Public Health in Malaysia - Che Musa, Muhd Firdaus (IIUM Journal of Orofacial and Health Sciences, 2022)
The continued recognition of Dental Public Health as one speciality in dentistry provides an opportunity for the speciality to rediscover and re-evaluate itself. As a discipline, public health dentistry evolved for many years to address the issues faced by our dynamic society, particularly Malaysia. Increased investment is necessary to see a tangible improvement in oral health. In this light, public health dentistry represents the nation’s dental conscience, as changes in DPH mirror both changes in society and the dental practice. Prevention and access to dental care for the underprivileged groups are as pertinent as providing medical and dental care for people with infectious diseases. Changes could be implemented through national oral health objectives and strategies and a myriad of new financing mechanisms. Despite the progressive changes in today’s world, the speciality’s goal to improve the public’s oral health and its commitment to work through ‘organised community efforts’ to achieve this goal remains. This article highlights the need for a long-term solution that could ensure the sustainability of DPH in Malaysia. It empowers DPH specialists to use their expertise for patients’ benefit across the three pillars of public health - health improvement, care, and protection. This could be achieved through the support of the dental community.